2012
DOI: 10.1111/j.1365-2656.2012.02030.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dispersal distance in mammals: a trait‐based approach

Abstract: Summary1. Dispersal is one of the principal mechanisms influencing ecological and evolutionary processes but quantitative empirical data are unfortunately scarce. As dispersal is likely to influence population responses to climate change, whether by adaptation or by migration, there is an urgent need to obtain estimates of dispersal distance. 2. Cross-species correlative approaches identifying predictors of dispersal distance can provide much-needed insights into this data-scarce area. Here, we describe the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 99 publications
5
125
1
Order By: Relevance
“…We found significant phylogenetic conservation in time-partitioning strategy within mammals as a whole ( (35), and 0.84 for dispersal distance (36). The global distributions of species richness within temporal niches, however, vary strikingly ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…We found significant phylogenetic conservation in time-partitioning strategy within mammals as a whole ( (35), and 0.84 for dispersal distance (36). The global distributions of species richness within temporal niches, however, vary strikingly ( Fig.…”
Section: Resultsmentioning
confidence: 84%
“…These variance/ randomization tests were significant for all seven continuous characters, except for distance ratio. Thus, all continuous characters, except for one, have phylogenetic signal, which thereby supported the use of phylogenies in their comparative tests [13]. Figure 1).…”
Section: Variance/randomization Tests Of the Distance Mass And Ratimentioning
confidence: 80%
“…Conversely, previous studies of species-specific dispersal have focused instead on the potential effects of other life history traits such as body size and territory area [9][10][11]. In particular, prior species-specific investigations have found that the natal dispersal distances (hereafter, referred to as distances) of a group are positively correlated with body size [12,13]. In animals, one explanation for this positive correlation is that the mass-specific energy cost of transport (COT) decreases with body size, thereby making it relatively cheaper for larger species to move farther [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short dispersal distances mean that declining populations may not be sustained by immigration, and that recolonisation following local extinction may not occur (Brown and Kodric-Brown, 1977). Considering that dispersal distances are not available for most of the species considered here, the home range diameter was used as a proxy of the vagility of each species (Bright, 1993;Whitmee and Orme, 2013;Santini et al, 2013). This was calculated from the mean home range area by assuming that the range was circular, and for riparian species the total length of the linear range was used (Bright, 1993).…”
Section: Factors and Variablesmentioning
confidence: 99%